Analysis of Types of Physical Activity on Active Elderly Community in Bandung City - Kamli Suwandi; Jajat Jajat; Ahmad Hamidi (UNIB Press, 2024)
Physical activity can improve health and reduce the risk of some diseases, and most importantly it can improve the quality of life of the elderly. The purpose of this study was to determine the level of physical activity and the type of physical activity carried out by the elderly daily in the elderly community in Bandung City. The method used is descriptive with a quantitative approach. This data collection technique used a purposive sampling technique, and the level of physical activity was measured using the International Physical Activity Questionnaire-Short Form (IPAQ-SF) questionnaire. The sample of this study was 40 people consisting of the Pasir Layung Elderly Community 20 people and the Setiabudhi Healthy Heart Community 20 people. The results of this study are that the majority of the elderly do physical activity every day, namely gymnastics as much as 75% and the majority of the elderly in this community have a high level of physical activity as much as 52%. It is proven that the elderly here have a high level of physical activity and have good physical activity.